Design of Regenerative Damper for Energy Harvester in Playground Seesaw - Reyhan Ramadhan; Muhammad Ul Haq; Estiyanti Ekawati; Tri Prakosa (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Increasing demand for electricity, coupled with a greater understanding of the environmental impact of conventional power generation, has led to growing research interest on alternative energy sources. Energy harvesters based on playground equipment, such as the seesaw, has been proposed as an alternative method to generate electrical power. In this study, a new harvesting mechanism based on the electromagnetic regenerative damper is proposed as an alternative method to harness energy from a playground seesaw. The proposed design is intended for higher power output and efficiency, smaller dimensions, and ease of installation on a seesaw. Lab tests have been carried out to characterize the proposed design experimentally. The energy harvesting (stroke velocity-to-voltage) coefficient for the proposed seesaw-based energy harvester is obtained as 73.18 V/(ms -1 ). The regenerative damper is capable of producing up to 110 mW of power at 9.34% efficiency.